Total War and Limited Government: The German Catholic Debate at the Dawn of the Nuclear Age - Hollerich, Michael J. (Theology and World Politics, 2020)
The chapter recovers the debate among German Catholics over North Atlantic Treaty Organization (NATO’s) introduction of tactical nuclear weapons into the new West German army (Bundeswehr). Young Catholic scholars Ernst-Wolfgang Böckenförde and Robert Spaemann forcefully opposed nuclear weaponry in debate with German theologian Gustav Gundlach. The arguments turned chiefly on natural law and papal authority, less so on theology. The chapter reconstructs the argument and recasts it in terms of political theology, a category that seems well suited for thinking about an issue of such gravity and finality (nuclear apocalypse being the ultimate Schmittian exception) and which the authors knew but avoided because of its discrediting under Nazism. The birth of a critical political theology in the 1960s enabled thinking about creation and divine sovereignty that could argue the case and exploit Catholicism’s global standing without lapsing into pre-critical biblical interpretation and philosophical methods ill-equipped to think about nuclear war.